Investigation of daytime wetting: when is spinal cord imaging indicated?. Issue 2 (1st August 2002) - Wraige, E; Borzyskowski, M
Abstract : Background: Most children with daytime wetting have detrusor instability. A minority have neuropathic vesicourethral dysfunction. The commonest cause is spina bifida, which may be closed. Clinical features suggestive of closed spina bifida include cutaneous, neuro-orthopaedic or lumbosacral spine x ray abnormalities, impaired bladder sensation, and incomplete bladder emptying. MRI is the ideal method for detecting spinal cord abnormality. It has been suggested that MRI spine is an unnecessary investigation in children with daytime wetting in the absence of cutaneous, neuro-orthopaedic, or lumbosacral spine x ray abnormalities. Aim: To clarify indications for magnetic resonance imaging (MRI) of the spine in children with voiding dysfunction. Methods: Retrospective study of children with voiding dysfunction referred from the Guy's Hospital neurourology clinic for MRI spine between April 1998 and April 2000. Clinical notes and results of investigations, including urodynamic studies and MRI spine were reviewed. Results: There were 48 children (median age 9.1 years). Closed spina bifida was detected in five, of whom four had neuropathic vesicourethral dysfunction confirmed by urodynamic studies. Impaired bladder sensation and incomplete bladder emptying were more frequent in these children than in those with normal MRI spine. One child with spinal cord abnormality had no cutaneous, neuro-orthopaedic, or lumbosacral spine x ray abnormalities. Conclusion: Spinal cord imaging should be considered in children with daytime wetting when this is associated with impaired bladder sensation or poor bladder emptying, even in the absence of neuro-orthopaedic, cutaneous, or lumbosacral spine x ray abnormalities.